Prevalence and pathogenicity of fungi associated with grapevine trunk diseases in Jordan - Firas M. ABU EL SAMEN; Marwa NASRALLAH; Mahmoud A. ALFAQIH; Kholoud M. ALANANBEH (Phytopathologia Mediterranea)
Grapevines (Vitis vinifera) are important fruit producers in Jordan, and grapevine trunk diseases (GTDs) are suspected to cause problems in many Jordanian vineyards. This study aimed to estimate GTDs incidence and severity in selected vineyards, and to isolate and identify the causal agents associated with GTDs in this country. Field surveys were carried out and representative samples of diseased vines showing GTDs symptoms were collected to isolate and identify the causal organisms. Molecular analyses of DNA sequences of the Internal Transcribed Spacer (ITS) regions of fungal ribosomal DNA (rDNA) were used to confirm the morphological identifications of the fungal isolates. GTDs were present in all the surveyed vineyards. Mean GTD incidence was 44% across all the fields evaluated, ranging from 9 to 69% in individual vineyards. Disease severity ranged from 52–74% (mean = 62%) across all vineyards and locations. A total of 325 fungal isolates were recovered from infected grapevines. The most prevalent pathogens identified were those associated with Botryosphaeria dieback, including Diplodia seriata, Lasiodiplodia theobromae and Neofusicoccum parvum, followed by the Esca disease pathogens Phaeoacremonium parasiticum, P. aleophilum, P. rubrigenum, and Fomitiporia spp. Ilyonectria liriodendri and I. spp., known to be associated with black foot of grapevines, were also isolated. Plant pathogens causing vascular wilts and root rots, including Fusarium proliferatum, F. oxysporum, Verticillium spp., and Rhizoctonia solani, were also identified from diseased plant samples, and were found in mixed infections with GTDs pathogens. Most of the identified pathogens, except those associated with vascular wilt and root rot, are reported for the first time in Jordan. Results of this study indicate that GTDs are widespread in Jordan, and that there is urgent need to adopt a “national strategy” for GTD management in this country.